Durability of ferro cement structures in aggressive environment by laboratory tests - Hanafiah, Faizal Md; Ramli, Mahyuddin; Nik Abllah, Nik Fuaad (Penerbit Universiti Sains Malaysia, 2004)
The climate in marine environment, an area of interface between the land and sea, remains highly humid and corrosive. Strength loss and corrosion in materials result due to the effect of the marine environment. Hence, the marine climate calls for renovation and development of new marine resistant engineering materials of specific properties.